PERAN GURU DALAM MENERAPKAN KEAMANAN DIGITAL PADA SISWA SEKOLAH DASAR - Sartika Pramita Bahri (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
This study examines the concept of digital security and the role of teachers in implementing digital security in elementary schools, as well as the challenges teachers face in their role as educators. This research employs a qualitative method, specifically a literature review approach. The objective of this study is to analyze the understanding of digital security, examine the role of teachers in its implementation in elementary schools, and identify the various challenges faced in enhancing students’ digital literacy. To shape the character of Indonesia’s “Golden Generation” of 2045 a generation excelling in all aspects and globally competitive the understanding of the four pillars of literacy must be applied across all levels of education: digital competence, digital security, digital culture, and digital ethics. Teachers play a key role in enhancing students’ understanding of digital literacy, particularly digital security. Understanding digital security helps mitigate digital threats such as the leakage of personal information (name, mother’s maiden name, date of birth, address, phone number, and so on) for criminal purposes, online fraud via social media, the spread of negative content, and fake news. On the other hand, teachers face challenges that hinder their ability to implement digital security, including technological disparities between schools, uneven teacher knowledge due to a lack of teacher training, and administrative systems. The results of this study highlight the importance of equitable access to facilities and infrastructure, intensive training for all teachers, and alignment between national and local policies. Ultimately, digital security can be effectively implemented in elementary schools across all regions. ABSTRAK Studi ini meneliti tentang pengertian keamanan digital dan peran guru dalam menerapkan keamanan digital di sekolah dasar serta kendala yang dihadapi guru sebagai seorang pendidik. Penelitian ini menggunakan metode kualitatif, yaitu pendekatan studi kepustakaan. Tujuan penelitian ini adalah untuk menganalisis pemahaman keamanan digital, mengkaji peran guru dalam penerapannya di sekolah dasar, serta mengidentifikasi berbagai kendala yang dihadapi dalam upaya meningkatkan literasi digital siswa. Untuk membentuk karakter generasi emas Indonesia 2045 yang memiliki keunggulan dalam segala aspek dan berdaya saing pada level global, pemahaman empat pilar literasi yang diaplikasikan dalam semua jenjang pendidikan yaitu kecakapan digital, keamanan digital, budaya digital, dan etika digital. Peran guru menjadi kunci dalam meningkatkan pemahaman siswa dalam literasi digital, salah satunya adalah keamanan digital. Pemahaman keamanan digital akan mereduksi ancaman digital seperti kebocoran informasi pribadi (Nama, nama ibu kandung, tanggal lahir, alamat, nomor telepon, dan lain sebagainya) untuk tindak kriminal, penipuan online melalui media sosial, penyebaran konten-konten negatif dan berita hoaks. Di sisi lain, guru menghadapi tantangan yang memengaruhi mereka dalam mengimplementasikan keamanan digital, antara lain kesenjangan teknologi antar sekolah, pengetahuan guru yang tidak merata akibat minimnya pelatihan guru, dan sistem administrasi. Hasil penelitian ini mengungkapkan pentingnya pemerataan sarana dan prasarana, pelatihan yang intensif bagi semua guru, dan keselarasan kebijakan nasional dan kebijakan lokal. Pada akhirnya, keamanan digital dapat terlaksana dengan baik di sekolah dasar di masing-masing daerah.